Replantation of a Partially Amputated Paw following Traumatic Laceration - Robertson, Heather M.; Degner, D. A.; Walshaw, R. (Veterinary and Comparative Orthopaedics and Traumatology, 1999)
Survival of the distal limb is dependent on the integrity of its vascular supply. Microvascular anastomosis of the median and caudal interosseus arteries following traumatic laceration of the palmar carpal region is described. Nine months after the operation, the dog was noted to have full function of the limb.
Keywords: Traumatic laceration; microvascular anastomosis; palmar carpus